2013
DOI: 10.5194/tc-7-599-2013
|View full text |Cite
|
Sign up to set email alerts
|

Surface mass balance model intercomparison for the Greenland ice sheet

Abstract: Abstract. A number of high resolution reconstructions of the surface mass balance (SMB) of the Greenland ice sheet (GrIS) have been produced using global re-analyses data extending back to 1958. These reconstructions have been used in a variety of applications but little is known about their consistency with each other and the impact of the downscaling method on the result. Here, we compare four reconstructions for the period 1960-2008 to assess the consistency in regional, seasonal and integrated SMB componen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
176
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(190 citation statements)
references
References 51 publications
14
176
0
Order By: Relevance
“…At the regional scale, the simulated SMB agrees relatively well with RCM results (Supplementary Figure S6, Tedesco and Fettweis, 2012;Vernon and others, 2013), except in the northern and western regions, where the simulated melting is overestimated (Supplementary Figure S6). We simulated negative SMB values in the northern and northeastern basins, while Vernon and others (2013) and Tedesco and Fettweis (2012) simulated SMB values close to zero, but positive.…”
Section: Surface Mass Balancesupporting
confidence: 71%
“…At the regional scale, the simulated SMB agrees relatively well with RCM results (Supplementary Figure S6, Tedesco and Fettweis, 2012;Vernon and others, 2013), except in the northern and western regions, where the simulated melting is overestimated (Supplementary Figure S6). We simulated negative SMB values in the northern and northeastern basins, while Vernon and others (2013) and Tedesco and Fettweis (2012) simulated SMB values close to zero, but positive.…”
Section: Surface Mass Balancesupporting
confidence: 71%
“…In this case we compare the EC-Earth-driven scenarios relative to the corresponding EC-Earth-driven present-day run; although, when doing so, one implicitly ignores potential nonlinearities whereby the magnitude of climate change can depend on the reference state (e.g., Boberg and Christensen 2012;Fettweis et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…By fitting a second-degree polynomial to annual SMB values for the two time slices for the RCP8.5 scenario relative to the historical period, we estimate the cumulative change in SMB for the 2011-2100 period. Here, we interpret this cumulative change in SMB as a change in ice-sheet thickness (in a manner similar to what was done in the final sensitivity experiments in Fettweis et al 2013). If the resulting surface lowering exceeds the ice-sheet thickness (Morlighem et al 2014) for a specific grid cell, that grid cell is then shown as a nonglacial grid cell in Figure 9.…”
Section: Climate Change On the Ice Sheetmentioning
confidence: 99%
See 2 more Smart Citations